Genomic analysis of multidrug-resistant Escherichia coli isolated from dairy cows in Shihezi city, Xinjiang, China - Bello, Abdullahi; Ning, Siqi; Zhang, Qi; Ni, Wei; Hu, Shengwei (Frontiers in Microbiology, 2025)
IntroductionDairy farming plays a vital role in agriculture and nutrition; however, the emergence of antimicrobial resistance (AMR) among bacterial pathogens poses significant risks to public health and animal welfare. Multidrug-resistant (MDR) Escherichia coli strains are of particular concern due to their potential for zoonotic transmission and resistance to multiple antibiotics. In this study, we investigated the prevalence of AMR and analyzed the genomes of two MDR E. coli isolated from dairy cows in Shihezi City.MethodsFecal samples were collected from dairy cows, and E. coli strains were isolated. Antibiotic susceptibility testing was conducted using the Kirby-Bauer disk diffusion method against 14 antibiotics. Two MDR isolates (E.coli_30 and E.coli_45) were selected for whole-genome sequencing and comparative genomic analysis. The Comprehensive Antibiotic Resistance Database (CARD) was used to identify AMR genes, and virulence factors were analyzed. Phylogenetic analysis was performed to determine the evolutionary relationships of the isolates, and a pangenome analysis of 50 E. coli strains was conducted to assess genetic diversity. The presence of mobile genetic elements (MGEs), including insertion sequences (IS) and transposons, was also examined.ResultsAmong the E. coli isolates, 22.9% exhibited MDR, with high resistance to imipenem and ciprofloxacin, while gentamicin and tetracycline remained the most effective antibiotics. Genomic analysis revealed key AMR genes, including mphA, qnrS1, and blaCTX-M-55 (the latter found only in E.coli_45), conferring resistance to macrolides, quinolones, and beta-lactams, respectively. Virulence genes encoding type III secretion systems (TTSS) and adhesion factors were identified, indicating pathogenic potential. Phylogenetic analysis showed that E.coli_30 and E.coli_45 originated from distinct ancestral lineages. The presence of two extended-spectrum β-lactamase (ESBL) genes in E.coli_45 was noticeable, so we studied their global and national distribution using evolutionary analysis. We found that they are endemic in E. coli, Salmonella enterica, and Klebsiella pneumoniae. Pangenome analysis revealed significant genetic diversity among E. coli strains, with unique genes related to metabolism and stress response. This indicates the bacteria’s adaptation to various environments. MGEs were identified as key contributors to genetic variability and adaptation.DiscussionThis study highlights the growing threat of MDR E. coli in dairy farms, emphasizing the critical role of MGEs in the spread of resistance genes. The genetic diversity observed suggests strong adaptive capabilities, justifying the need for continuous AMR surveillance in livestock. Effective monitoring and mitigation strategies are essential to prevent the dissemination of MDR bacteria, thereby protecting both animal and public health.